Creating a project office for implementing survey works of complex infrastructure objects of a capital construction on the basis of works’ decomposition - M. S. Perfiliev (Вестник СибАДИ, 2017)
The article dwells on the formation of the project office for implementing survey works of complex infrastructure objects of capital construction. General principles of forming the project office are formulated; its organizational structure is also provided. Options proposed for appointment to the post of chief engineer of the complex project. The author suggests variants of appointing workers on the position of a chief engineer of a complex project. The author has determined functions of the project office’s workers, managing survey works. In the conclusion the author provides recommendations on forming control commands and organization of survey works on large scale infrastructure objects.